Black Muslims and the Law civil liberties from Elijah Muhammad to Muhammad Ali - Crawford, Malachi D. (Critical Africana studies, 2015)
Black Muslims and the Law examines the Nation of Islam's struggle for religious freedom from World War II to the Vietnam War through the lives of key members, such as Elijah Muhammad and Muhammad Ali. In doing so, the work reveals the key initiatives the Nation of Islam took to defend the civil liberties of its members from a position of power.